CHALLENGES FACING INSURANCE BROKERS IN KENYA - Kajwang, Ben (European Journal of Business and Strategic Management, 2021)
Purpose: The insurance industry, like other industries, has faced obstacles that have threatened its productivity, profitability, and capacity to compete against its rivals. The objective of this study to identify and discuss the challenges facing insurance brokers in Kenya. The aim of this work is to enable the readers understand the various challenges facing insurance brokers and their impact on the insurance industry. Methodology: A desktop literature review was used for this purpose. Relevant seminal references and journal articles for the study were identified using Google Scholar. The inclusion criteria entailed papers that were not over five years old. Findings: The study concluded that customer experience & satisfaction, workflow inefficiency, uncertainties in the market, unfavorable government regulation, cybersecurity risk and lead generation are some of the challenges that affect insurance brokers in Kenya. These challenges have greatly been influenced by the ever-changing technology that has revolutionized the workforce labour and business activities generally in all organizations and government influence on the regulations set by the Insurance Regulatory Authority. Unique contribution to theory, practice and policy: The study therefore recommended that insurance brokers should embrace the use of well-developed digital services that will enable them service their customers efficiently and meet their needs while the Insurance Regulatory Authority should come up with strategies that will help mitigate the unfavorable government regulations that affect insurance brokers.